1995
DOI: 10.1055/s-2007-1013791
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Cavoatrial Extension of Malignant Tumors

Abstract: Surgical management for cavoatrial involvement of malignant tumors and its outcome is reported on for 6 patients; their age ranged from 55 to 79 years and 5 were male and 1 female. The basic disease was renal cell carcinoma in 5 cases and adrenal leiomyosarcoma in 1. Intracaval tumor extension was diagnosed by computed tomography, magnet resonance imaging, digital subtraction angiography, and echocardiography. The tumor was resected together with adherant vena cava and invaded right-atrial wall, using cardiopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…[ 45 ] 1995 30 M Pain (abdominal) L 11 ND Operative pathology SMA Adrenalectomy Alive 20 Hayashi J. [ 46 ] 1995 55 F Pain (abdominal) and fever R ND IVC, hepatic vein and right atrium Operative pathology ND Adrenalectomy + nephrectomy Alive 52 Lack EE. [ 3 ] 1991 49 M Pain (flank) R 11 None Operative pathology SMA, vimentin and actin Adrenalectomy + nephrectomy, chemotherapy and radiation Alive 9 Choi SH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ] 1995 30 M Pain (abdominal) L 11 ND Operative pathology SMA Adrenalectomy Alive 20 Hayashi J. [ 46 ] 1995 55 F Pain (abdominal) and fever R ND IVC, hepatic vein and right atrium Operative pathology ND Adrenalectomy + nephrectomy Alive 52 Lack EE. [ 3 ] 1991 49 M Pain (flank) R 11 None Operative pathology SMA, vimentin and actin Adrenalectomy + nephrectomy, chemotherapy and radiation Alive 9 Choi SH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cavoatrial thrombosis occurs in approximately 6% of patients with RCC. [1] The classification of caval thrombi in RCC is as follows: Level 1, venous thrombus in the renal vein that does not extended to the IVC; Level 2, infrahepatic IVC thrombus; Level 3, retro-or suprahepatic thrombus that does not reach the right atrium; and Level 4, thrombus in the right atrium. [8] All RCCs with a thrombus in the IVC and without metastasis require surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cavoatrial thrombi occur in approximately 6% of patients with a renal-cell carcinoma (RCC). [1] Although cavoatrial thrombi may occur in renal tumors, the absence of distant metastases still allows radical surgery techniques to be employed. In the surgical treatment of patients with renal tumors and caval thrombi at multiple levels, cardiopulmonary bypass (CPB) with or without hypothermic circulatory arrest is used.…”
mentioning
confidence: 99%
“…6 Multiple authors have described resection of similar lesions using total body deep hypothermic circulatory arrest (DHCA). [7][8][9][10][11] Other authors have utilized cardiopulmonary bypass without DHCA. 12 In this case, 2 novel techniques were employed.…”
Section: Discussionmentioning
confidence: 99%